Versification : metrics in practice - Frog; Grünthal, Satu; Kallio, Kati; Niemi, Jarkko (Studia Fennica, ISSN 1458-5278, 2021)
Abstract.
Keywords: versifikaatio; metriikka; runomitat; suullinen perinne; runomuotoinen perinne; lyriikka; kieli ja kielet; versifikation; metrik; versmått; muntlig tradition; tradition i versform; lyrik; språk